Micromechanics of oil palm mesocarp fibres and biocomposites - Hanipah, Suhaiza Hanim (2018)
Investigation was conducted on non-linear mechanical behaviour of oil palm mesocarp fibres (OPMF) and their biocomposites, with focus on the interface of the fibres (filler) and matrix. Viscoelastic with damage was observed from tensile tests conducted under cyclic mode, as reported from the unloadingreloading results of the cyclic tests at larger deformations (2 and 3mm deformation). This behaviour was related to the lignocellulosic components of the fibres, as well as geometry of the fibres consisting of silica bodies and cellular structure. On the other hand, mechanical tests comparison of the processed fibres mentioned before with fresh mesocarp fibres showed different viscoelastic behaviour of the latter fibres, which was due to moisture within the fibres containing palm oil, as well as the effect of oil palm processing that altered the processed fibres. The tests results were modelled through a viscoelastic model available in finite element software, Abaqus, which consisted of hyperelastic model with Prony series and a stress softening function. Good agreement was reported from the fitting of the model to the mechanical tests results, highlighting the viscoelastic behaviour of oil palm fibres. Emphasis was then given to the effect of silica bodies towards integrity of the oil palm fibres, where a cohesive zone modelling (CZM) was included to model the interface between silica bodies and fibres. The results showed minimal effect of silica bodies towards integrity of the fibres as a whole, which was due to the silica bodies were only partly embedded on the outer surface of the fibres. The fibres were then used for biocomposites development as filler, and LLDPE was used as matrix. The interface between the filler and matrix was improved using anhydrate (maleic anhydride and itaconic anhdride). In addition to the interface improvement using chemical method (anhydrate to strengthen the filler-matrix interface), it is hypothesised that the geometric effect of the fibres consisting of silica bodies on the surface can also improve the filler-matrix interface. Therefore, the fibres were not chemically treated (with alkali or acid as conducted before in previous literatures) to preserve the silica bodies and fibres integrity. Improvement of the biocomposites with both anhydrate and silica bodies was reported from a series of experiments, namely mechanical tests, FTIR, and microscopy analyses. In particular, SEM image showed that silica bodies left craters after being pull during tensile testing, suggesting that the silica bodies prevent sliding between the filler-matrix interface. Likewise, evidence of OH bond between the silica bodies and matrix was shown, similar to the filler-matrix improvement due to addition of anhydrate. Biocomposites finite element model geometry was generated using Digimat software, but the modelling analysis was terminated before any results can be obtained. The results from both mechanical behaviour of fibres and biocomposites interface highlighted that oil palm mesocarp fibres behaved as a viscoelastic material with damage due to deformation, and the fibres used for biocomposites application can be obtained directly without chemical treatment.